Rhinovirus-induced VP1-specific Antibodies are Group-specific and Associated With Severity of Respiratory Symptoms - Katarzyna Niespodziana; Clarissa R. Cabauatan; David J. Jackson; Daniela Gallerano; Belen Trujillo-Torralbo; Ajerico del Rosario; Patrick Mallia; Rudolf Valenta; Sebastian L. Johnston (EBioMedicine, 2015)
Background: Rhinoviruses (RVs) are a major cause of common colds and induce exacerbations of asthma and chronic inflammatory lung diseases. Methods: We expressed and purified recombinant RV coat proteins VP1-4, non-structural proteins as well as N-terminal fragments of VP1 from four RV strains (RV14, 16, 89, C) covering the three known RV groups (RV-A, RV-B and RV-C) and measured specific IgG-subclass-, IgA- and IgM-responses by ELISA in subjects with different severities of asthma or without asthma before and after experimental infection with RV16. Findings: Before infection subjects showed IgG1 > IgA > IgM > IgG3 cross-reactivity with N-terminal fragments from the representative VP1 proteins of the three RV groups. Antibody levels were higher in the asthmatic group as compared to the non-asthmatic subjects. Six weeks after infection with RV16, IgG1 antibodies showed a group-specific increase towards the N-terminal VP1 fragment, but not towards other capsid and non-structural proteins, which was highest in subjects with severe upper and lower respiratory symptoms. Interpretation: Our results demonstrate that increases of antibodies towards the VP1 N-terminus are group-specific and associated with severity of respiratory symptoms and suggest that it may be possible to develop serological tests for identifying causative RV groups.